Gas diffusion layer with uniform porous structure for hydrogen fuel cell and preparation method of gas diffusion layer

Through the combination technology of modified carbon fiber and conductive adhesive, a hydrogen fuel cell gas diffusion layer with uniform hydrophobic and conductive properties was prepared, which solved the problem of insufficient conductivity of the gas diffusion layer in the prior art, and significantly improved the current distribution. Uniformity and stability of the equipment.

CN119400888APending Publication Date: 2025-02-07JIANGSU SHANGYI HYDROGEN ENERGY TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411564549.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The hydrophobic properties and conductivity of the gas diffusion layer in existing hydrogen fuel cells need to be further improved, resulting in uneven current distribution and increasing the risk of overheating and damage.

Method used

Using modified carbon fiber as the frame material of the base layer, through surface chemical deposition repair and modified polyacrylonitrile fibrosis, carbonization, oxidation and other steps, a uniform hydrophobic layer and conductive layer are formed, and conductive carbon black is introduced into the microporous layer. , hydrophobic agent and conductive adhesive, and a conductive, breathable, thermally conductive and hydrophobic gas exchange layer is prepared by spraying and high-temperature curing.

Benefits of technology

The conductivity and thermal conductivity of the gas diffusion layer are significantly improved, the uniformity of the current distribution is ensured, the risk of overheating and damage is reduced, and the overall performance of the gas diffusion layer is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400888A_ABST
    Figure CN119400888A_ABST
Patent Text Reader

Abstract

The invention discloses a gas diffusion layer with a uniform porous structure for a hydrogen fuel cell and a preparation method of the gas diffusion layer, which are used for solving the technical problem that the hydrophobicity and the conductivity of the gas diffusion layer need to be further improved. The carbon fiber paper comprises a substrate layer and a microporous layer, when the raw paper of the carbon fiber paper is prepared, modified carbon fibers and a conductive adhesive form a chemical bond cross-linked structure, a large number of self-assembled silver particles are introduced as decarboxylation sites, oxygen-containing functional groups are left to form oxygen doping on the carbon surface, defects and active sites are generated, and the carbon fiber paper is prepared. The nano-silver particles are melted at high temperature to repair defects generated in the decarboxylation process, so that the electric conduction and heat conduction performance of the substrate layer is remarkably enhanced, sulfur groups on the surface of the nano-silver particles are doped into a lattice structure of carbon fibers in the graphitization process, the energy band structure of the carbon material is changed, the migration rate of electrons is increased, and the performance of the carbon material is improved. And further processing to obtain a conductive, breathable, heat-conducting and hydrophobic high-porosity gas exchange layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fuel cells, and in particular to a gas diffusion layer with a uniform porous structure for a hydrogen fuel cell and a preparation method thereof. Background Art

[0002] In hydrogen fuel cells, the uniform porous structure design of the gas diffusion layer has been continuously optimized to improve the performance and stability of the fuel cell. Early gas diffusion layers were mostly made of carbon paper or carbon cloth materials, which had limited porosity and uneven pore size distribution, resulting in poor gas diffusion and water management effects.

[0003] To solve this problem, researchers gradually introduced a double-layer structure of micropores and macropores, optimizing gas diffusion and water discharge by regulating the porosity, pore size distribution and hydrophilicity of the material. This series of developments enabled the gas diffusion layer to achieve higher gas diffusion efficiency and water management capabilities at high current density, providing support for the long-term and high efficiency of hydrogen fuel cells.

[0004] Prior art CN112421059A discloses a gas diffusion layer and a preparation method thereof. The preparation method of the gas diffusion layer comprises the following steps: adding a conductive material to a carbon fiber suspension slurry to obtain a carbon fiber substrate, treating the carbon fiber substrate to obtain a conductive porous substrate, forming a hydrophobic layer on the conductive porous substrate to obtain a hydrophobic conductive porous substrate, and forming a microporous layer on the hydrophobic conductive porous substrate to obtain a gas diffusion layer. In the process of preparing the carbon fiber substrate, the conductive material is directly added to the carbon fiber suspension slurry so that the conductive material can be evenly distributed inside the carbon fiber substrate, the conductive material and the carbon fiber can be better combined, and the carbon fiber substrate as a whole has conductivity, thereby improving the performance of the gas diffusion layer.

[0005] However, the above patent content is to directly add conductive materials into the carbon fiber suspension to obtain the carbon fiber substrate. However, since the surface of the carbon fiber is extremely rough and the friction between the materials causes uneven dispersion of the materials, the conductive properties of the materials need to be further improved. Ultimately, the conductive properties of the materials vary with different positions, resulting in uneven current distribution, causing certain areas to carry too high current, increasing the risk of overheating and damage, and ultimately causing local overload.

[0006] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention

[0007] The object of the present invention is to provide a gas diffusion layer with a uniform porous structure for a hydrogen fuel cell and a preparation method thereof, so as to solve the technical problem that the hydrophobicity and electrical conductivity of the gas diffusion layer in the prior art need to be further improved.

[0008] The object of the present invention can be achieved by the following technical solution: A gas diffusion layer with a uniform porous structure for a hydrogen fuel cell, comprising a substrate layer and a microporous layer;

[0009] The preparation method of the base layer comprises the following steps:

[0010] A1. Add modified carbon fiber, polyethylene oxide and deionized water into a reactor and stir. After stirring for 5-10 minutes at room temperature, add a conductive adhesive solution into the reactor and perform post-processing to obtain a carbon fiber paper base.

[0011] A2, vacuum impregnating the carbon fiber paper base paper in a conductive adhesive solution for 1-2 hours, and then post-treating to obtain a base layer;

[0012] The microporous layer is composed of conductive carbon black, hydrophobic agent and conductive adhesive in a dosage ratio of 4-6g:1-2g:3-5g.

[0013] The reaction principle for preparing the base layer is as follows: the organic precursor in the carbon fiber base paper is carbonized at a high temperature of 800-850°C to remove the impurities therein, thereby increasing the carbon content of the material and forming a disordered carbon structure. Next, it is graphitized in an extremely high temperature environment of 2000°C, and the carbon atoms are gradually arranged into a hexagonal network of graphite microcrystalline structures, which significantly improves the crystallinity of the material.

[0014] Furthermore, in step A1, the modified carbon fiber, polyethylene oxide, deionized water and conductive adhesive solution are used in a ratio of 10-12 g: 0.8-1.2 g: 30-40 mL: 10-12 mL, and the conductive adhesive solution is prepared by mixing the conductive adhesive and ethanol in a ratio of 2-3 g: 10 mL. The post-treatment includes: the mixed solution is dispersed by a deflaker to obtain a uniform mixed fiber slurry, which is poured into a rapid paper sheet former for wet forming and drying to obtain Carbon fiber paper base paper; in step A2, post-treatment includes: after impregnation, placing the material in a hot press, controlling the pressure of the hot press to 3-5MPa, the temperature to 60-80°C, hot pressing for 30-40min to obtain a cured base paper, placing the cured base paper in a tubular furnace, introducing nitrogen protection, heating the temperature to 800-850°C at a rate of 5°C / min, keeping the temperature for 1-2h, and then continuing to heat the temperature to 2000°C, keeping the temperature for 2-4h to obtain a base layer.

[0015] Furthermore, the preparation method of the modified carbon fiber comprises the following steps:

[0016] B1, adding modified polyacrylonitrile to a melt spinning machine, extruding through a spinneret into deionized water at a temperature of 20-30° C., cooling, and rapidly solidifying to obtain a carbon fiber precursor;

[0017] B2. Add the carbon fiber precursor into the tubular furnace, introduce oxygen to exhaust the air, raise the temperature of the tubular furnace to 200-300°C under the oxygen atmosphere, keep it warm for 1-2 hours, cut off the oxygen, introduce nitrogen protection into the tubular furnace, continue to raise the temperature of the reactor to 600-800°C, keep it warm for 2-4 hours, then raise the temperature of the tubular furnace to 1200-1600°C, keep it warm for 4-6 hours, and obtain carbon fiber;

[0018] The reaction principle for preparing carbon fiber is as follows: the furnace temperature is raised to 200-300°C in an oxygen atmosphere to allow the precursor material to undergo a preliminary oxidation cross-linking reaction to enhance the thermal stability of the material; after the preliminary oxidation is completed, the oxygen supply is cut off, nitrogen is introduced to form an inert protective environment, and the temperature of the tube furnace is continued to be raised to 600-800°C for a deep carbonization reaction. During this stage, non-carbon heteroatoms in the precursor material are gradually removed, and the carbon content is significantly increased. Finally, the temperature of the tube furnace is raised to 1200-1600°C to allow the carbon atoms to further rearrange and graphitize at high temperature to form carbon fibers with a certain orientation and structure.

[0019] B3, adding carbon fiber and oxidation liquid into a reactor and stirring, raising the temperature of the reactor to 30-40°C, keeping warm and stirring for 10-20 minutes, and post-treating to obtain oxidized carbon fiber;

[0020] The reaction principle for preparing oxidized carbon fibers is to introduce active functional groups, such as hydroxyl, carboxyl and epoxy groups, onto the surface of the carbon fibers through oxidation with an oxidizing liquid.

[0021] B4. Add the assembled fibers into a vapor deposition device to obtain modified carbon fibers through vapor deposition.

[0022] The reaction principle for preparing modified carbon fiber is as follows: after high-temperature vapor deposition, the voids and defects on the surface of the oxidized carbon fiber are repaired, and finally a fluorine-containing hydrophobic layer is formed to obtain the modified carbon fiber.

[0023] Further, in step B1, the temperature of the melt spinning machine is set to 250-300°C, and the nozzle diameter is 200-400μm; in step B2, the heating rate of the tubular furnace is 5°C / min; in step B3, the stirring rate of the reactor is 80-120rpm, the amount ratio of carbon fiber and oxidation liquid is 1-2g:8-10mL, and the oxidation liquid is prepared by 98wt% concentrated sulfuric acid and 65-68wt% nitric acid solution in a volume ratio of 3-4:1. The post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered To room temperature, filter the reaction liquid and collect the filter cake, wash the filter cake with ethanol and deionized water for 3-5 times, and then place the filter cake in a drying oven at a temperature of 60°C and vacuum dry it until the filter cake has a constant weight to obtain oxidized carbon fiber; in step B4, the vapor deposition operation is as follows: after nitrogen is introduced to exhaust the air in the reaction chamber, the temperature of the reaction chamber is increased to 800-1200°C, the air pressure is set to 1000-1200Pa, and carbon tetrafluoride is introduced at a gas flow rate of 600-800sccm, and the heat treatment is carried out for 2-4h to obtain modified carbon fiber.

[0024] Furthermore, the preparation method of modified polyacrylonitrile is: add N-allyl-2,2,2-trifluoroacetamide, 2-methyl-3-phenyl-2-acrylonitrile, 2-(trifluoromethyl)acrylic acid, azobisisobutyronitrile and dichloroethane into a reactor, increase the temperature of the reactor to 50-70°C, keep the reaction warm for 2-4 hours, and post-treat to obtain modified polyacrylonitrile.

[0025] The reaction equation for preparing modified polyacrylonitrile is:

[0026]

[0027] Where:

[0028] The reaction principle for preparing modified polyacrylonitrile is as follows: under the catalysis of azobisisobutyronitrile and high temperature, the carbon-carbon double bonds of N-allyl-2,2,2-trifluoroacetamide, 2-methyl-3-phenyl-2-acrylonitrile and 2-(trifluoromethyl)acrylic acid are broken to generate free radicals, which are continuously polymerized to form modified polyacrylonitrile.

[0029] Furthermore, the amount ratio of N-allyl-2,2,2-trifluoroacetamide, 2-methyl-3-phenyl-2-acrylonitrile, 2-(trifluoromethyl)acrylic acid, azobisisobutyronitrile and dichloroethane is 5-8g:4-6g:6-8g:0.3-0.5g:60-80mL, and the post-treatment includes: after the reaction kettle is completed, the temperature of the reaction kettle is lowered to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 80-100°C, and the reduced pressure distillation is carried out until no liquid is produced to obtain modified polyacrylonitrile.

[0030] Furthermore, the preparation method of the conductive adhesive is:

[0031] C1. Add silver nanoparticles, thioglycolic acid, triethylamine and ethanol into a reaction kettle and stir, raise the reaction temperature to 40-60° C., keep the temperature for 30-40 minutes, and perform post-treatment to obtain self-assembled silver particles;

[0032] The reaction equation for preparing self-assembled silver particles is:

[0033]

[0034] Where: represents nanosilver particles; Represents self-assembled silver particles.

[0035] The reaction principle for preparing self-assembled silver particles is: under alkaline conditions, the thiol bonds continuously react with the silver atoms on the surface of the nano-silver particles, and finally the self-assembled silver particles are prepared.

[0036] C2. Add the self-assembled silver particles and epoxy resin into a reaction kettle, raise the temperature of the reaction kettle to 80-100° C., and stir for 30-40 minutes to obtain a conductive adhesive.

[0037] Furthermore, in step C1, the amount ratio of the nanosilver particles, thioglycolic acid, triethylamine and ethanol is 8-10g:2-3g:0.3-0.5g:40-60mL, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, the filter cake is washed with deionized water and ethanol for 3-5 times, and then the filter cake is transferred to a drying oven at a temperature of 60°C and vacuum dried until the filter cake has a constant weight to obtain self-assembled silver particles; in step C2, the amount ratio of the self-assembled silver particles and the epoxy resin is 40-60g:40-60g.

[0038] The present invention also provides a method for preparing a gas diffusion layer with a uniform porous structure for a hydrogen fuel cell, comprising the following steps:

[0039] S1, mixing conductive carbon black, a hydrophobic agent and a conductive adhesive to obtain a conductive coating;

[0040] S2. Spraying the conductive coating on the base layer to obtain a microporous layer, and then curing at high temperature to obtain a gas diffusion layer.

[0041] Furthermore, in step S1, the hydrophobic agent is one or more of polytetrafluoroethylene, polyvinylidene fluoride and ethylene propylene fluoride; in step S2, the spraying operation is: placing the conductive coating in a hot melt sprayer at a temperature of 80-100°C and a spraying pressure of 1-3MPa; the high temperature curing operation is: transferring the material to a hot press, controlling the hot press pressure to 3-5MPa and a temperature of 60-80°C, and hot pressing for 30-40 minutes to obtain a gas diffusion layer.

[0042] The present invention has the following beneficial effects:

[0043] 1. In the process of preparing the gas exchange layer, the modified carbon fiber repaired by surface chemical deposition is prepared, and the friction force in the dispersion system is weakened to make it fully dispersed. In the process of obtaining the carbon fiber paper base paper by blending and dispersing, the active groups on the modified carbon fiber and a large number of epoxy groups in the conductive adhesive form a structure cross-linked by chemical bonds to ensure the integrity of the carbon fiber paper structure, and a large number of self-assembled silver particles are introduced as decarboxylation sites, leaving oxygen-containing functional groups on the carbon surface to form oxygen doping, generate defects and redox active sites, and improve electrochemical activity. The nano silver particles melt at high temperature to repair the defects generated in the decarboxylation process, so that the electrical conductivity and thermal conductivity of the base layer are significantly enhanced. A large number of sulfur groups on the surface are doped into the lattice structure of the carbon fiber during the graphitization process to change the band structure of the carbon material, improve the migration rate of electrons, and enhance the electrical conductivity of the carbon fiber paper. The conductive adhesive is mixed with the conductive carbon black and the hydrophobic agent to obtain a conductive coating, which is sprayed on the base layer and cured to finally prepare a conductive, breathable, thermally conductive and hydrophobic high-porosity gas exchange layer.

[0044] 2. In the process of preparing the conductive adhesive, the present invention first forms a coating layer on the surface of the nanosilver particles through in-situ self-assembly to obtain self-assembled silver particles, thereby improving the dispersibility and stability of the nanosilver particles in the epoxy resin. The epoxy resin molecules form a three-dimensional network structure during the cross-linking process, so that the conductive carbon black particles in the microporous layer are more stably combined. At the same time, the network structure generated by the cross-linking reaction limits the excessive filling of the resin, thereby forming a uniform porous structure, which is conducive to the diffusion of gas. The surface of the nanosilver particles is assembled and modified in situ and contains a large number of carboxyl groups. These groups enhance the interaction with the conductive carbon black, improve the dispersibility of the adhesive in the microporous layer, reduce the agglomeration of the resin, and the nanosilver particles can be evenly distributed in the microporous layer without causing blockage of the pores, thereby ensuring that the gas diffusion channel is unobstructed.

[0045] 3. In the process of preparing the gas exchange layer of the present invention, a modified carbon fiber is first prepared as the framework material of the base layer. The modified carbon fiber forms a uniform hydrophobic layer on the surface through fiberization, carbonization, oxidation and vapor deposition repair of modified polyacrylonitrile; in the process of preparing the modified polyacrylonitrile, amide groups, benzene rings, carboxyl groups and a large number of fluorine groups are introduced into its organic chain segments by selecting reaction monomers. During the carbonization process, the amide groups decompose at high temperature and undergo dehydration reactions to promote the nucleation process of carbon. The nitrogen atoms introduced during the decomposition of the amide groups produce nitrogen-doped carbon materials to improve the electrical conductivity of the carbon materials. The stable conjugated structure of the benzene ring tends to maintain its structure during the high-temperature carbonization process and is gradually converted into a graphitized structure, so that the carbonization yield and quality of the material are relatively high. The fluorine groups enter the graphitized lattice structure during the carbonization process, which helps to keep the surface dry and prevent moisture from accumulating in the material, thereby improving the gas transmission efficiency and durability of the material in a humid environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0047] Figure 1 This is a schematic diagram of the overall three-dimensional structure of the gas diffusion layer prepared by the present invention;

[0048] In the figure: 100, base layer; 200, microporous layer. DETAILED DESCRIPTION

[0049] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0050] Example 1

[0051] This embodiment provides a method for preparing a gas diffusion layer with a uniform porous structure for a hydrogen fuel cell, comprising the following steps:

[0052] S1 Preparation of modified carbon fiber

[0053] Weigh: 20.0 g N-allyl-2,2,2-trifluoroacetamide, 15.0 g 2-methyl-3-phenyl-2-acrylonitrile, 20.0 g 2-(trifluoromethyl)acrylic acid, 1.2 g azobisisobutyronitrile and 180.0 mL ethylene dichloride, add to a reactor and stir, raise the temperature of the reactor to 50° C., keep warm and stir for 2 h, after the reactor is completed, lower the temperature of the reactor to room temperature, add the reaction solution to a rotary evaporator with a water bath temperature of 80° C., and distill under reduced pressure until no liquid is produced to obtain modified polyacrylonitrile;

[0054] The modified polyacrylonitrile was added into a melt spinning machine, the temperature of the melt spinning machine was set to 250°C, the nozzle diameter was 200 μm, and the fiber precursor was obtained by extruding it through a spinneret into deionized water at a temperature of 20°C and cooling it, and then rapidly solidifying it to obtain fiber precursor. After the reaction was completed, the temperature of the reactor was lowered to room temperature, and the reaction liquid was filtered to collect the filter cake. After the filter cake was washed 3 times with ethanol and deionized water, the filter cake was placed in a drying oven at a temperature of 60°C and vacuum dried until the filter cake had a constant weight, thereby obtaining oxidized carbon fiber.

[0055] The carbon fiber precursor was added into the tubular furnace, oxygen was introduced to exhaust the air, and the temperature of the tubular furnace was raised to 200°C at a heating rate of 5°C / min under the oxygen atmosphere. After keeping the temperature for 1 hour, the oxygen was cut off, and nitrogen was introduced into the tubular furnace for protection. The temperature of the reactor was further raised to 600°C, and after keeping the temperature for 2 hours, the temperature of the tubular furnace was raised to 1200°C and kept for 4 hours to obtain the carbon fiber.

[0056] Weigh: 12.0 mL 98 wt % concentrated sulfuric acid and 4.0 mL 65 wt % nitric acid solution to prepare an oxidizing solution;

[0057] Weigh: 6.0 g of carbon fiber and 24.0 mL of oxidizing solution were added to the reactor and stirred at a stirring rate of 80 rpm. The temperature of the reactor was raised to 30°C and stirred for 10 min. After the reaction was completed, the temperature of the reactor was lowered to room temperature, the reaction liquid was filtered to collect the filter cake, and the filter cake was washed with ethanol and deionized water for 3 times, and then placed in a drying oven at a temperature of 60°C and vacuum dried until the filter cake had a constant weight to obtain oxidized carbon fiber;

[0058] The assembled fibers were added into a vapor deposition device. After nitrogen was introduced to exhaust the air in the reaction chamber, the temperature of the reaction chamber was raised to 800°C, the gas pressure was set to 1000 Pa, and carbon tetrafluoride was introduced at a gas flow rate of 600 sccm. The heat treatment was carried out for 2 hours to obtain modified carbon fibers.

[0059] S2. Preparation of base layer

[0060] Weigh: 30.0 g of nanosilver particles, 9.0 g of thioglycolic acid, 1.2 g of triethylamine and 120.0 mL of ethanol, add them into a reactor and stir, raise the reaction temperature to 40° C., and keep the reaction temperature for 30 minutes. After the reaction is completed, lower the temperature of the reactor to room temperature, filter the reaction liquid to collect the filter cake, wash the filter cake with deionized water and ethanol for 3 times, transfer the filter cake to a drying oven at 60° C. and vacuum dry it until the filter cake has a constant weight, to obtain self-assembled silver particles;

[0061] Weigh: 40.0 g of self-assembled silver particles and 60.0 g of epoxy resin are added into a reaction kettle, the temperature of the reaction kettle is raised to 80° C., and the mixture is stirred for 30 min to obtain a conductive adhesive;

[0062] Weigh: 25.0 g of conductive adhesive and 100.0 mL of ethanol to prepare a conductive adhesive solution;

[0063] Weigh: 30.0g modified carbon fiber, 3.0g polyethylene oxide, 100.0mL deionized water, add to the reactor and stir, stir at room temperature for 5min, add 30.0mL conductive adhesive solution to the reactor, disperse the mixed solution by a deflaker to obtain a uniform mixed fiber slurry, pour into a rapid paper former for wet forming and drying, and obtain carbon fiber paper base paper;

[0064] After the carbon fiber paper base paper is vacuum impregnated in the conductive adhesive solution for 1 hour, the material is placed in a hot press, and the pressure of the hot press is controlled to be 5 MPa and the temperature is 60°C. After hot pressing for 30 minutes, a cured base paper is obtained. The cured base paper is placed in a tubular furnace, and nitrogen is introduced for protection. The temperature is increased to 800°C at a rate of 5°C / min. After keeping the temperature for 1 hour, the temperature is continued to be increased to 2000°C and kept for 2 hours to obtain a base layer 100.

[0065] S3. Preparation of gas exchange layer

[0066] Weigh: 25.0 g of conductive carbon black, 8.0 g of polytetrafluoroethylene and 18.0 g of conductive adhesive and mix them evenly to obtain a conductive coating;

[0067] The conductive coating was placed in a hot melt sprayer at a temperature of 80°C and a spraying pressure of 1 MPa, and sprayed on the base layer 100 to obtain a microporous layer 200. The material was transferred to a hot press, and the pressure of the hot press was controlled to be 5 MPa and the temperature to be 60°C. After hot pressing for 30 minutes, a gas diffusion layer was obtained.

[0068] Example 2

[0069] This embodiment provides a method for preparing a gas diffusion layer with a uniform porous structure for a hydrogen fuel cell, comprising the following steps:

[0070] S1 Preparation of modified carbon fiber

[0071] Weigh: 24.0g N-allyl-2,2,2-trifluoroacetamide, 16.0g 2-methyl-3-phenyl-2-acrylonitrile, 20.0g 2-(trifluoromethyl)acrylic acid, 1.2g azobisisobutyronitrile and 200.0mL dichloroethane, add to the reactor and stir, raise the temperature of the reactor to 70°C, keep warm and stir for 4h, after the reactor is completed, wait for the temperature of the reactor to be lowered to room temperature, add the reaction liquid to a rotary evaporator with a water bath temperature of 100°C, and distill under reduced pressure until no liquid is produced to obtain modified polyacrylonitrile;

[0072] The modified polyacrylonitrile was added into a melt spinning machine, the temperature of the melt spinning machine was set to 300°C, the nozzle diameter was 400 μm, and the fiber precursor was obtained by extruding it through a spinneret into deionized water at a temperature of 30°C and cooling it, and then rapidly solidifying it to obtain fiber precursor. After the reaction was completed, the temperature of the reactor was lowered to room temperature, and the reaction liquid was filtered to collect the filter cake. After the filter cake was washed 5 times with ethanol and deionized water, the filter cake was placed in a drying oven at a temperature of 60°C and vacuum dried until the filter cake had a constant weight, thereby obtaining oxidized carbon fiber.

[0073] The carbon fiber precursor was added into the tubular furnace, oxygen was introduced to exhaust the air, and the temperature of the tubular furnace was raised to 300°C at a heating rate of 5°C / min under the oxygen atmosphere. After keeping the temperature for 2 hours, the oxygen was cut off, and nitrogen was introduced into the tubular furnace for protection. The temperature of the reactor was further raised to 800°C, and after keeping the temperature for 4 hours, the temperature of the tubular furnace was raised to 1600°C and kept for 6 hours to obtain the carbon fiber.

[0074] Weigh: 30.0 mL 98 wt % concentrated sulfuric acid and 10.0 mL 68 wt % nitric acid solution to prepare an oxidizing solution;

[0075] Weigh: 18.0 g of carbon fiber and 96.0 mL of oxidizing solution were added to the reactor and stirred at a stirring rate of 120 rpm. The temperature of the reactor was raised to 40°C and stirred for 20 min. After the reaction was completed, the temperature of the reactor was lowered to room temperature, the reaction liquid was filtered to collect the filter cake, and the filter cake was washed 5 times with ethanol and deionized water, and then placed in a drying oven at a temperature of 60°C and vacuum dried until the filter cake had a constant weight to obtain oxidized carbon fiber;

[0076] The assembled fibers were added into a vapor deposition device. After nitrogen was introduced to exhaust the air in the reaction chamber, the temperature of the reaction chamber was raised to 1200°C, the gas pressure was set to 1200 Pa, and carbon tetrafluoride was introduced at a gas flow rate of 800 sccm. The heat treatment was carried out for 4 hours to obtain modified carbon fibers.

[0077] S2. Preparation of base layer

[0078] Weigh: 28.0 g of nanosilver particles, 8.0 g of thioglycolic acid, 1.5 g of triethylamine and 150.0 mL of ethanol, add them into a reactor and stir, raise the reaction temperature to 60° C., and keep the temperature for 40 minutes. After the reaction is completed, lower the temperature of the reactor to room temperature, filter the reaction liquid to collect the filter cake, wash the filter cake with deionized water and ethanol for 5 times, transfer the filter cake to a drying oven at 60° C. and vacuum dry it until the filter cake has a constant weight, to obtain self-assembled silver particles;

[0079] Weigh: 60.0 g of self-assembled silver particles and 40.0 g of epoxy resin are added into a reaction kettle, the temperature of the reaction kettle is raised to 100° C., and the mixture is stirred for 40 minutes to obtain a conductive adhesive;

[0080] Weigh: 27.0 g of conductive adhesive and 100.0 mL of ethanol to prepare a conductive adhesive solution;

[0081] Weigh: 30.0g modified carbon fiber, 3.0g polyethylene oxide, 100.0mL deionized water, add to the reactor and stir, stir for 10min at room temperature, add 32.0mL conductive adhesive solution to the reactor, disperse the mixed solution by a deflaker to obtain a uniform mixed fiber slurry, pour into a rapid paper former for wet forming and drying, and obtain carbon fiber paper base paper;

[0082] After the carbon fiber paper base paper is vacuum impregnated in the conductive adhesive solution for 2 hours, the material is placed in a hot press, and the pressure of the hot press is controlled to be 5 MPa and the temperature is 80°C. After hot pressing for 40 minutes, a cured base paper is obtained. The cured base paper is placed in a tubular furnace, and nitrogen is introduced for protection. The temperature is increased to 850°C at a rate of 5°C / min, and after keeping the temperature for 2 hours, the temperature is continued to be increased to 2000°C and kept for 4 hours to obtain a base layer 100.

[0083] S3. Preparation of gas exchange layer

[0084] Weigh: 21.0 g of conductive carbon black, 7.2 g of polytetrafluoroethylene and 18.0 g of conductive adhesive and mix them evenly to obtain a conductive coating;

[0085] The conductive coating was placed in a hot melt sprayer at a temperature of 100°C and a spraying pressure of 3MPa, and sprayed on the base layer 100 to obtain a microporous layer 200. The material was transferred to a hot press, and the hot press pressure was controlled to be 5MPa and the temperature was 80°C. After hot pressing for 40 minutes, a gas diffusion layer was obtained.

[0086] Example 3

[0087] This embodiment provides a method for preparing a gas diffusion layer with a uniform porous structure for a hydrogen fuel cell, comprising the following steps:

[0088] S1 Preparation of modified carbon fiber

[0089] Weigh: 27.0 g N-allyl-2,2,2-trifluoroacetamide, 21.0 g 2-methyl-3-phenyl-2-acrylonitrile, 28.0 g 2-(trifluoromethyl)acrylic acid, 1.8 g azobisisobutyronitrile and 240.0 mL ethylene dichloride, add to a reactor and stir, raise the temperature of the reactor to 60° C., keep warm and stir for 3 hours, after the reactor is completed, lower the temperature of the reactor to room temperature, add the reaction solution to a rotary evaporator with a water bath temperature of 90° C., and distill under reduced pressure until no liquid is produced to obtain modified polyacrylonitrile;

[0090] The modified polyacrylonitrile was added into a melt spinning machine, the temperature of the melt spinning machine was set to 275°C, the nozzle diameter was 300 μm, and it was extruded through the spinneret into deionized water at a temperature of 25°C and cooled, and rapidly solidified to obtain fiber precursors. After the reaction was completed, the temperature of the reactor was lowered to room temperature, the reaction liquid was filtered to collect the filter cake, and the filter cake was washed 4 times with ethanol and deionized water, and then placed in a drying oven at a temperature of 60°C and vacuum dried until the filter cake had a constant weight, to obtain oxidized carbon fiber;

[0091] The carbon fiber precursor was added into the tubular furnace, oxygen was introduced to exhaust the air, and the temperature of the tubular furnace was raised to 250°C at a heating rate of 5°C / min under the oxygen atmosphere. After keeping the temperature for 1.5 hours, the oxygen was cut off, and nitrogen was introduced into the tubular furnace for protection. The temperature of the reactor was further raised to 700°C, and after keeping the temperature for 3 hours, the temperature of the tubular furnace was raised to 1500°C and kept for 2 hours to obtain the carbon fiber.

[0092] Weigh: 32.0 mL 98 wt % concentrated sulfuric acid and 10.0 mL 66 wt % nitric acid solution to prepare an oxidizing solution;

[0093] Weigh: 18.0 g of carbon fiber and 96.0 mL of oxidizing solution were added to the reactor and stirred at a stirring rate of 100 rpm. The temperature of the reactor was raised to 36 ° C. and stirred for 15 min. After the reaction was completed, the temperature of the reactor was lowered to room temperature, the reaction liquid was filtered to collect the filter cake, and the filter cake was washed with ethanol and deionized water for 4 times, and then placed in a drying oven at a temperature of 60 ° C. and vacuum dried until the filter cake had a constant weight to obtain oxidized carbon fiber;

[0094] The assembled fibers were added into a vapor deposition device. After nitrogen was introduced to exhaust the air in the reaction chamber, the temperature of the reaction chamber was raised to 1000°C, the gas pressure was set to 1100 Pa, and carbon tetrafluoride was introduced at a gas flow rate of 700 sccm. The heat treatment was carried out for 3 hours to obtain modified carbon fibers.

[0095] S2. Preparation of base layer

[0096] Weigh: 36.0 g of nanosilver particles, 12.0 g of thioglycolic acid, 1.8 g of triethylamine and 180.0 mL of ethanol, add them into a reactor and stir, raise the reaction temperature to 50° C., and keep the reaction temperature for 36 minutes. After the reaction is completed, lower the temperature of the reactor to room temperature, filter the reaction liquid to collect the filter cake, wash the filter cake with deionized water and ethanol for 4 times, transfer the filter cake to a drying oven at a temperature of 60° C. and vacuum dry it until the filter cake has a constant weight, to obtain self-assembled silver particles;

[0097] Weigh: 60.0 g of self-assembled silver particles and 40.0 g of epoxy resin are added into a reaction kettle, the temperature of the reaction kettle is raised to 90° C., and the mixture is stirred for 36 minutes to obtain a conductive adhesive;

[0098] Weigh: 28.0 g of conductive adhesive and 100.0 mL of ethanol to prepare a conductive adhesive solution;

[0099] Weigh: 32.0g modified carbon fiber, 3.6g polyethylene oxide, 100.0mL deionized water, add to the reactor and stir, stir at room temperature for 8min, add 32.0mL conductive adhesive solution to the reactor, disperse the mixed solution by a deflaker to obtain a uniform mixed fiber slurry, pour into a rapid paper former for wet forming and drying, and obtain carbon fiber paper base paper;

[0100] After the carbon fiber paper base paper is vacuum impregnated in the conductive adhesive solution for 1.5 hours, the material is placed in a hot press, and the pressure of the hot press is controlled to be 5 MPa and the temperature is 70°C. After 36 minutes, the cured base paper is obtained. The cured base paper is placed in a tubular furnace, and nitrogen is introduced for protection. The temperature is increased to 825°C at a rate of 5°C / min, and after keeping the temperature for 1.5 hours, the temperature is continued to be increased to 2000°C and kept for 3 hours to obtain the base layer 100.

[0101] S3. Preparation of gas exchange layer

[0102] Weigh: 21.0 g of conductive carbon black, 7.2 g of polytetrafluoroethylene and 18.0 g of conductive adhesive and mix them evenly to obtain a conductive coating;

[0103] The conductive coating was placed in a hot melt sprayer at a temperature of 90°C and a spraying pressure of 2MPa, and sprayed on the base layer 100 to obtain a microporous layer 200. The material was transferred to a hot press, and the pressure of the hot press was controlled to be 4MPa and the temperature to be 70°C. After hot pressing for 36 minutes, a gas diffusion layer was obtained.

[0104] Comparative Example 1

[0105] The difference between this comparative example and Example 3 is that step S1 is eliminated and an equal amount of carbon fiber is used to replace the modified carbon fiber.

[0106] Comparative Example 2

[0107] The difference between this comparative example and Example 3 is that the step of preparing the conductive adhesive in step S2 is eliminated, and an equal amount of phenolic resin is used to replace the conductive adhesive in the process of preparing the base layer.

[0108] Comparative Example 3

[0109] The difference between this comparative example and Example 3 is that in step S3, an equal amount of phenolic resin is used to replace the conductive adhesive in the process of preparing the microporous layer.

[0110] Performance Test:

[0111] The plane resistivity, vertical resistivity, air permeability, porosity and thermal conductivity of the gas exchange layers prepared in Examples 1-3 and Comparative Examples 1-3 were tested with reference to the standard GB / T 20042.7-2014 "Proton Exchange Membrane Fuel Cell Part 7: Test Method for Carbon Paper Characteristics";

[0112] The water permeability pressure and critical wettability value of the gas exchange layer prepared in Examples 1-3 and Comparative Examples 1-3 were tested with reference to the standard GB / T 42270-2022 “Test method for hydrophobic properties of porous hydrophobic membranes”. The specific data are shown in Table 1.

[0113] Table 1-Performance test data of each sample

[0114]

[0115] Data Analysis:

[0116] Comparing and analyzing the data in Table 1 above, the gas exchange layer prepared by the present invention has a plane resistivity of 3.2 mΩ·cm, a vertical resistivity of 152.7 mΩ·cm, and a permeability of 3812 mL·mm·(cm 2 ·h·mmHg) -1 , porosity 89.2%, thermal conductivity 1.6W·(m·k) -1 , the water permeability pressure is 0.4MPa and the critical wetness value is 41.2μm. All performance test data are better than the control example.

[0117] Explanation analysis:

[0118] In the process of preparing the gas exchange layer, the modified carbon fiber repaired by surface chemical deposition is prepared, the friction force of the modified carbon fiber in the dispersion system is weakened, and the modified carbon fiber is fully dispersed. In the process of obtaining the carbon fiber paper base paper by blending and dispersing, the active groups on the modified carbon fiber and a large number of epoxy groups in the conductive adhesive form a structure cross-linked by chemical bonds, thereby ensuring the integrity of the carbon fiber paper structure, and a large number of self-assembled silver particles are introduced as decarboxylation sites, leaving oxygen-containing functional groups on the carbon surface to form oxygen doping, generate defects and redox active sites, and improve the electrochemical activity. The nano silver particles melt at high temperature to repair the defects generated in the decarboxylation process, so that the electrical conductivity and thermal conductivity of the base layer are significantly enhanced. A large number of sulfur groups on the surface are doped into the lattice structure of the carbon fiber during the graphitization process, so as to change the energy band structure of the carbon material and improve the migration rate of electrons, thereby enhancing the electrical conductivity of the carbon fiber paper. The conductive adhesive is mixed with the conductive carbon black and the hydrophobic agent to obtain a conductive coating, which is sprayed on the base layer and cured to finally prepare a conductive, air-permeable, thermally conductive and hydrophobic high-porosity gas exchange layer.

[0119] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

[0120] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0121] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A gas diffusion layer with a uniform porous structure for a hydrogen fuel cell, characterized in that: It comprises a base layer (100) and a microporous layer (200); The method for preparing the base layer (100) comprises the following steps: A1. Add modified carbon fiber, polyethylene oxide and deionized water into a reactor and stir. After stirring for 5-10 minutes at room temperature, add a conductive adhesive solution into the reactor and perform post-processing to obtain a carbon fiber paper base. A2, vacuum impregnating the carbon fiber paper base paper in a conductive adhesive solution for 1-2 hours, and then post-treating the base paper to obtain a base layer (100); The microporous layer (200) is composed of conductive carbon black, a hydrophobic agent and a conductive adhesive in a dosage ratio of 4-6 g: 1-2 g: 3-5 g.

2. A gas diffusion layer with a uniform porous structure for a hydrogen fuel cell according to claim 1, characterized in that: In step A1, the modified carbon fiber, polyethylene oxide, deionized water and conductive adhesive solution are used in a ratio of 10-12 g: 0.8-1.2 g: 30-40 mL: 10-12 mL, and the conductive adhesive solution is prepared by mixing the conductive adhesive and ethanol in a ratio of 2-3 g: 10 mL. The post-treatment includes: the mixed solution is dispersed by a deflaker to obtain a uniform mixed fiber slurry, which is poured into a rapid paper sheet former for wet forming and drying to obtain a carbon fiber. Paper base paper; in step A2, post-treatment includes: after the impregnation is completed, placing the material in a hot press, controlling the pressure of the hot press to be 3-5MPa, the temperature to be 60-80°C, hot pressing for 30-40min to obtain a solidified base paper, placing the solidified base paper in a tubular furnace, introducing nitrogen protection, heating the temperature to 800-850°C at a heating rate of 5°C / min, keeping the temperature for 1-2h, and then continuing to heat the temperature to 2000°C, keeping the temperature for 2-4h to obtain a base layer.

3. The gas diffusion layer with uniform porous structure for hydrogen fuel cell according to claim 1, characterized in that: The preparation method of the modified carbon fiber comprises the following steps: B1, adding modified polyacrylonitrile to a melt spinning machine, extruding through a spinneret into deionized water at a temperature of 20-30° C., cooling, and rapidly solidifying to obtain a carbon fiber precursor; B2. Add the carbon fiber precursor into the tubular furnace, introduce oxygen to exhaust the air, raise the temperature of the tubular furnace to 200-300°C under the oxygen atmosphere, keep it warm for 1-2 hours, cut off the oxygen, introduce nitrogen protection into the tubular furnace, continue to raise the temperature of the reactor to 600-800°C, keep it warm for 2-4 hours, then raise the temperature of the tubular furnace to 1200-1600°C, keep it warm for 4-6 hours, and obtain carbon fiber; B3, adding carbon fiber and oxidation liquid into a reactor and stirring, raising the temperature of the reactor to 30-40°C, keeping warm and stirring for 10-20 minutes, and post-treating to obtain oxidized carbon fiber; B4. Add the assembled fibers into a vapor deposition device to obtain modified carbon fibers through vapor deposition.

4. A gas diffusion layer with a uniform porous structure for a hydrogen fuel cell according to claim 3, characterized in that: In step B1, the temperature of the melt spinning machine is set to 250-300°C, and the nozzle diameter is 200-400μm; in step B2, the heating rate of the tubular furnace is 5°C / min; in step B3, the stirring rate of the reactor is 80-120rpm, the amount ratio of carbon fiber and oxidizing solution is 1-2g:8-10mL, and the oxidizing solution is prepared by 98wt% concentrated sulfuric acid and 65-68wt% nitric acid solution in a volume ratio of 3-4:1; in step B4, the vapor deposition operation is as follows: after nitrogen is introduced to exhaust the air in the reaction chamber, the temperature of the reaction chamber is increased to 800-1200°C, the air pressure is set to 1000-1200Pa, and carbon tetrafluoride is introduced at a gas flow rate of 600-800sccm, and the heat treatment is carried out for 2-4h to obtain modified carbon fiber.

5. A gas diffusion layer with a uniform porous structure for a hydrogen fuel cell according to claim 4, characterized in that: The preparation method of the modified polyacrylonitrile comprises: adding N-allyl-2,2,2-trifluoroacetamide, 2-methyl-3-phenyl-2-acrylonitrile, 2-(trifluoromethyl)acrylic acid, azobisisobutyronitrile and ethylene dichloride into a reaction kettle and stirring, raising the temperature of the reaction kettle to 50-70° C., stirring for 2-4 hours, and post-treating to obtain the modified polyacrylonitrile.

6. A gas diffusion layer with a uniform porous structure for a hydrogen fuel cell according to claim 5, characterized in that: The stirring rate of the reaction kettle is 80-120 rpm, and the usage ratio of N-allyl-2,2,2-trifluoroacetamide, 2-methyl-3-phenyl-2-acrylonitrile, 2-(trifluoromethyl)acrylic acid, azobisisobutyronitrile and dichloroethane is 5-8 g:4-6 g:6-8 g:0.3-0.5 g:60-80 mL.

7. The gas diffusion layer with uniform porous structure for hydrogen fuel cell according to claim 1, characterized in that: The preparation method of the conductive adhesive is as follows: C1. Add nanosilver particles, thioglycolic acid, triethylamine and ethanol into a reaction kettle and stir, raise the reaction temperature to 40-60° C., keep the temperature for 30-40 minutes, and perform post-treatment to obtain self-assembled silver particles; C2. Add the self-assembled silver particles and epoxy resin into a reaction kettle, raise the temperature of the reaction kettle to 80-100° C., and stir for 30-40 minutes to obtain a conductive adhesive.

8. A gas diffusion layer with a uniform porous structure for a hydrogen fuel cell according to claim 7, characterized in that: In step C1, the usage ratio of nano silver particles, thioglycolic acid, triethylamine and ethanol is 8-10 g: 2-3 g: 0.3-0.5 g: 40-60 mL; in step C2, the usage ratio of self-assembled silver particles and epoxy resin is 40-60 g: 40-60 g.

9. The method for preparing a gas diffusion layer with a uniform porous structure for a hydrogen fuel cell according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1, mixing conductive carbon black, a hydrophobic agent and a conductive adhesive to obtain a conductive coating; S2, spraying the conductive coating onto the base layer (100) to obtain a microporous layer (200), and then curing at high temperature to obtain a gas diffusion layer.

Citation Information

Patent Citations

  • Gas diffusion layer and preparation method

    CN112421059A